Implementation of the Development of PAI Learning Materials to Create Interesting and Meaningful Learning at Tunas Harapan Ar-Raudhah Elementary School, Bandung City - Yusuf Pardamean; Mulyawan Safwandy Mulyawan (UIN Sunan Gunung Djati Bandung, 2024)
In Islamic Religious Education, there is a need to innovate in the development of PAI teaching materials that are capable of creating interesting and meaningful learning. Looking at the current reality, it turns out that the quality of Islamic religious education still does not meet expectations. In its true sense, the goals of Islamic Religious Education have still not been achieved optimally. The aim of the research is to design an innovation strategy for developing PAI learning materials. In this research, the research method used is library research. In its implementation, the author collected data from several literary sources in the form of journals, theses, or other research related to learning concepts, constructivist learning theory and Islamic religious education. Furthermore, the results of the research regarding the implementation of PAI material development strategies in general can be said to be going well and in accordance with the implementation steps.